The Effect of Turmeric Filtrate Nanocapsule Levels in the Ration on Local Duck Meat Composition and Serum Cholesterol - Sundari , Sundari; Susiati, Anastasia Mamilisti; Faisal, Achmad (International Journal of Poultry Science, 2019)
Objective: This study aimed to determine the optimal level of supplementation with turmeric filtrate nanocapsules in rations and its effect on the meat composition (protein, fat, water, ash and serum cholesterol) of male local ducks. Materials and Methods: Sixty three male ducks were distributed in a completely randomized design. Data were analyzed using One-way ANOVA. The ducks aged 6-10 weeks were assigned to 21 cage units exposed to seven treatments (T), each with three replications of 3 ducks each. The treatments with turmeric filtrate nanocapsule or nanoparticle (NP) addition consisted of control basal ration (BR) without NP (T1); BR+1% NP (T2);BR+2% NP(T3); BR+3% NP(T4); BR+4% NP(T5); BR+5% NP(T6) and BR+6% NP(T7). The data were analyzed using analysis of variance followed by Duncan’s test when significant differences occurred. Results: The results showed that the treatment had a significant effect (p<0.05) on protein, fat and meat water content but a non-significant effect on meat ash content and serum cholesterol. Conclusion: The addition of5% turmeric filtrate nanocapsules in rations was the ideal level for increasing protein content and reducing fat content in the meat of local ducks.